Study of the properties of pectin substances for the production of healthy food products - A. V. Tarasenko (Новые технологии, 2024)
The article is devoted to the research in the field of using frozen grapes in the technology of production of products for a healthy diet. The main objectives of the research are to substantiate technological significance of frozen table grapes for the development of functional desserts. To study the influence of negative temperatures on the gelling and complexing ability of pectin substances in frozen grapes with subsequent defrosting of the raw material. The object of the research was table grapes of 5 varieties grown in the Krasnodar region. Experimental studies of technological and biochemical parameters of fresh and frozen grapes in order to study and confirm the use of grapes in the food industry for the development of desserts with different functional areas were carried out on the territory of the Kuban State Agrarian University named after I.T. Trubilin in the laboratories of the Faculty of Food Production and Biotechnology. Biochemical methods of analysis, generally accepted in the food industry, were used as research tools. It is well known that low-temperature freezing helps to maximize the preservation of the nutritional value of plant materials, however, in the health food industry, recipes and technologies for processing frozen grapes are practically not represented. An information search of scientific literature has shown that there are no studies on the study and selection of grape varieties for canning by freezing and the production of functional products from defrosted raw materials, which indicates the need to conduct experimental studies, study the kinetics of the chemical and biochemical composition of fresh, frozen and defrosted grapes in order to differentiate raw materials for the production of desserts with different functional orientations. Using biochemical analysis methods, it has been established that, regardless of varietal characteristics, the main components of the chemical composition of grapes are preserved during freezing and further defrosting.